Correct Answer - Option 2 : x

^{2}+ y

^{2}- 6x- 4y- 36 = 0

__Concept:__

Equation of circle having centre (h, k) and radius r is

** (x – h)**^{ 2} + (y – k)^{ 2} = r^{2 }

__Calculation:__

Given, centre of circle ( 3, 2) and radius 7 units

We know that , equation of circle is (x – h) 2 + (y – k) 2 = r2

According to the question, the equation of circle is

( x - 3 )^{2} + ( y - 2 )^{2} = 7^{2}

⇒ x^{2}+ 9 - 6x + y^{2}+ 4 - 4y = 49

⇒ **x**^{2} + y^{2}- 6x - 4y - 36 = 0.

**∴** **The correct option is 2. **